Servant subversions: reading the British anxiety over ‘Native Nuisance’ as infra-politics in Anglo-Indian household manuals - Banerjee, Francis; Das, Arindam (Penerbit Universiti Kebangsaan Malaysia, 2025)
The British colonial domestic space emerges as a critical site for interrogating the racialised dynamics of empire, owing to the proximity it fostered between the coloniser and the colonised. While extant scholarship predominantly underscores colonial hegemony and control within this space, our study, while acknowledging this premise, undertakes a contrapuntal, against-the-grain reading of Anglo-Indian domestic manuals to foreground the subversive agency of “native” servants. These manuals—produced between 1850 and 1900, a period roughly coterminous with the apogee of Victorian moralism and imperial confidence—serve not merely as instructional texts but as anxious colonial archives, inadvertently documenting servant resistance. Using a qualitative methodology grounded in close textual analysis, this study probes the discursive constructions of “native servant problems” as symptomatic of deeper tensions and anxieties embedded in the colonial household. By exposing the manuals’ aporias and symptomatic silences, we argue that seemingly mundane acts—such as feigned ignorance, strategic disobedience, delay, pilferage, and non-verbal defiance—constitute forms of infrapolitics that subtly unsettled the Anglo-Indian domestic order and, by extension, the colonial power matrix. The manuals analysed were selected based on their accessibility and availability, ensuring a representative sample of prescriptive domestic literature circulating during high imperialism. Our findings reveal that native servants were not passive subjects but stealth agents of disruption, whose infrapolitical manoeuvres subverted the performative authority of white domesticity. This reframing compels a reconsideration of the colonial household as a fraught space of power, negotiation, and everyday resistance.